Digital horizons in non-communicable disease care: a bibliometric exploration of intervention impact and innovation - Bhattacharya, Sudip; Singh, Alok; Kashyap, Akanksha (Frontiers in Digital Health, 2025)
IntroductionDigital interventions show considerable promise in managing non-communicable diseases (NCDs) within primary healthcare.AimThe aim of this study was to conduct a comprehensive bibliometric analysis of research on digital interventions for individuals living with NCDs.MethodologyThis study explores digital interventions in NCDs through a bibliometric analysis from 2014 to 2024. Carefully designed search queries targeted primary and combined terms to cover a wide range of NCDs, including cancer, diabetes, and hypertension. SCOPUS searches yielded 9,572 English-language articles, refined by excluding non-relevant works and duplicates. Metadata, including authorship, keywords, and citations, was extracted for analysis. Using Biblioshiny and VosViewer, the study examined publication trends, telemedicine applications, and the knowledge framework of the field. Conceptual themes were identified through co-occurrence mapping, intellectual structures via co-citation networks, and social structures through collaboration patterns among authors, institutions, and countries.ResultsThe upward trend in research on digital interventions and NCDs accelerated significantly after 2018, peaking in 2021, followed by a slight decline. Medicine dominates this field, with considerable contributions from biochemistry, health professions, and engineering. The most prolific authors, primarily from the United States, United Kingdom, and Australia, have significantly shaped this research area. Institutional contributions are led by Harvard Medical School and other global leaders, reflecting strong inter-institutional collaborations. The United States and the United Kingdom are the most productive countries, with the Journal of Medical Internet Research standing out as the leading publication. Keyword analysis reveals a focus on telemedicine, COVID-19, tele-health, and digital health. Co-citation analyses identify key intellectual frameworks, while co-authorship and institutional collaborations highlight robust global networks. Emerging trends emphasize AI, digital health tools, and patient self-management, underscoring a transformative shift in addressing NCDs through technology-driven interventions. The findings highlight the need for patient-centered applications, improved implementation strategies, and strengthened collaborations, especially in underrepresented regions, to enhance the global impact of digital interventions for NCDs.